β-Sitosterol Inhibits Rheumatoid Synovial Angiogenesis Through Suppressing VEGF Signaling Pathway - Qian, Kai; Zheng, Xue-Xia; Wang, Chen; Huang, Wen-Guang; Liu, Xiao-Bao; Xu, Shu-Di; Liu, Dan-Kai; Liu, Min-Ying; Lin, Chang-Song (Frontiers in Pharmacology, 2022)
Abstract: Background: Rheumatoid arthritis (RA) is a chronic disabling disease, which forms synovial angiogenesis with invasive nature and leads to joint destruction. Current pharmacotherapy is unsatisfactory for its special side effects and limitations. Although antiangiogenic therapy is regarded as a new potential therapy for RA, few drugs are available. Increasing studies have shown that β-sitosterol may have present inhibitory effects on angiogenesis, but its mechanisms in RA are still unclear. Methods: According to the results of gene set enrichment analysis (GSEA) of transcriptome data, which was performed in endothelial cells of RA patients, we used human umbilical vein endothelial cells (HUVECs) to evaluate the pharmacological effects of β-sitosterol on tube formation, cells proliferation, and migration. Furthermore, the action of β-sitosterol on VEGFR2/p-VEGFR2 was evaluated by molecular docking and Western blotting. Furthermore, synovial angiogenesis and joint destruction of the ankle were evaluated in the presence or absence of β-sitosterol in collagen-induced arthritis (CIA) mice, and the β-sitosterol on VEGFR2/p-VEGFR2 expression was verified by immunohistochemistry staining. Results: Tube formation and CD31 immunohistochemistry results identified that β-sitosterol inhibited angiogenesis in vitro and in vivo. 5-Ethynyl-2'-deoxyuridine (EDU) and cell cycle showed that β-sitosterol restrained the proliferation of HUVECs. Meanwhile, transwell and stress fibers revealed that β-sitosterol inhibited the migration of HUVECs. Compared with Axitinib, the inhibitory effect of β-sitosterol on VEGFR2/p-VEGFR2 had likeness. In the CIA mice, β-sitosterol also presented therapeutic effects on decreasing the swelling degree, ameliorating the damage of bone and cartilage, inhibiting the synovial angiogenesis of the ankle, and restraining the expression of VEGFR2 and p-VEGFR2 in the ankle. Conclusion: In summary, our data prove that β-sitosterol has a restrained effect on synovial angiogenesis, and alleviated joint swelling and bone destruction in CIA mice. Its underlying therapeutic mechanisms highly involved inhibited the activation of the VEGF signaling pathway.